Nuclear receptors for retinoic acid and thyroid hormone regulate transcription of keratin genes. - Tomic, M (1990)
In the epidermis, retinoids regulate the expression of keratins, the intermediate filament proteins of epithelial cells. We have cloned the 5' regulatory regions of four human epidermal keratin genes, K#5, K#6, K#10, and K#14, and engineered constructs in which these regions drive the expression of the CAT reporter gene. By co-transfecting the constructs into epithelial cells along with the vectors expressing nuclear receptors for retinoic acid (RA) and thyroid hormone, we have demonstrated that the receptors can suppress the promoters of keratin genes. The suppression is ligand dependent; it is evident both in established cell lines and in primary cultures of epithelial cells. The three RA receptors have similar effects on keratin gene transcription. Our data indicate that the nuclear receptors for RA and thyroid hormone regulate keratin synthesis by binding to negative recognition elements in the upstream DNA sequences of the keratin genes. RA thus has a twofold effect on epidermal keratin expression: qualitatively, it regulates the regulators that effect the switch from basal cell-specific keratins to differentiation-specific ones; and quantitatively, it determines the level of keratin synthesis within the cell by direct interaction of its receptors with the keratin gene promoters.